Study of The Effect of Renal Failure on The Concentration of HbA1c in Patients with Diabetes (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study was conducted at the Diabetes mellitus and Endocrinology and Renal Failure Centers in Al- Sader medical city including 60 patients from male and female, 30 patients have renal failure with Diabetes mellitus, other 30 patients have diabetes mellitus only. The age range from (30-65) years. The study lasted from November 2011 until March  2012.They were evaluated each of fasting blood sugar, urea, creatinine parameters in serum, and evaluated level of glycosylated hemoglobin in the blood.There was a significant increasing in each of blood sugar, urea, creatinine concentration in renal failure with diabetes mellitus patients as compared with diabetes mellitus patients. Also there was a significant decreases in percent of glycosylated hemoglobin in renal failure with diabetes mellitus patients as compared with diabetes mellitus patients.